Dermoid cyst of ovary misdiagnosed as intrauterine fetal demise: a case report - Varsha, Shanti Subedi; Deo, Anju; Sharma, Anjana; Ghimire, Sita (Journal of Nobel Medical College, 2012)
Thirty two years multipara with amenorrhoea of five months presented with bleeding per vagina for ten days. Clinically and radiologically she was diagnosed with intrauterine fetal demise at 20 weeks period of gestation. She was induced with prostaglandins continuously for seven days. On eighth day of admission features of uterine rupture was present. On laparotomy ruptured huge dermoid cyst with chemical peritonitis was discovered. There was no evidence of pregnancy. We are reporting this case for a rare complication of ruptured dermoid cyst and also to illustrate the importance of clinical assessment. DOI: http://dx.doi.org/10.3126/jonmc.v1i2.7305 Journal of Nobel Medical College (2012), Vol.1 No.2 p.82-83